2023
DOI: 10.1177/09564624231153202
|View full text |Cite
|
Sign up to set email alerts
|

Is U=U consistently known and implemented? A survey among different medical specialists in Brazil

Abstract: Despite solid scientific evidence, the concepts of treatment as prevention (TASP) and Undetectable = Untransmittable (U = U) remain unfamiliar and underutilized for some healthcare providers. We conducted a self-completion survey to evaluate the knowledge of TASP/U = U in different medical specialties. Wilcoxon Rank-Sum, Chi-square and Fisher’s exact tests were used for group comparisons and a logistic regression model was used to assess factors independently associated with U = U-non-supportive attitudes. 197… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Our study identified 26% of GPs were neutral towards or disagreed with U=U. Nunes et al 6 reported a similar result of 26% of health professionals in Brazil being neutral or disagreeing with U=U. The messages from doctors regarding HIV have been about using condoms since the 1980s, and this is entrenched, so it is difficult for GPs, especially with no training on the most updated science of HIV transmission, to believe in the accuracy of U=U.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Our study identified 26% of GPs were neutral towards or disagreed with U=U. Nunes et al 6 reported a similar result of 26% of health professionals in Brazil being neutral or disagreeing with U=U. The messages from doctors regarding HIV have been about using condoms since the 1980s, and this is entrenched, so it is difficult for GPs, especially with no training on the most updated science of HIV transmission, to believe in the accuracy of U=U.…”
Section: Discussionsupporting
confidence: 61%
“…A study from Brazil identified that 74% of healthcare providers agreed with U=U; however, only 66% strongly agreed or agreed that PLHIV should be informed about U=U. 6 Studies have reported barriers to communicating U=U from the healthcare providers' perspective. A UK study 7 identified the following barriers: hesitation with communicating zero transmission risk of HIV; and perceptions that clients may not want to hear this message.…”
mentioning
confidence: 99%
“…Even recognized health authorities continue to contribute to uncertainty and misunderstanding. For example, health care providers throughout the world refrain from or convolute delivery of the U=U message to patients, 16,19,20,33,34 and US health department websites communicate about U=U inconsistently, if at all. 21 Health authorities have sometimes used the terms "undetectable" and "virally suppressed" interchangeably 32,35 and have defined the terms according to variable numerical thresholds (eg, ,20, ,50, or ,200 copies/mL).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the article by Nunes and colleagues 1 addresses a very important issue that should not be underestimated. Their findings highlight the urgent need for improvement in medical education, where knowledge of the U=U concept should be disseminated and expanded.…”
mentioning
confidence: 89%
“…We read with great interest the recent article by Nunes and colleagues describing that the concepts of treatment as prevention and “Undetectable equals Untransmittable” (U=U) remain unfamiliar and underutilized by some Brazilian healthcare providers. 1 U=U is a prevention access campaign launched in 2016 by a group of HIV activists, aiming to “end the dual epidemics of HIV and HIV related stigma by empowering people with accurate and meaningful information”. 2 An undetectable viral load is generally defined as less than 200 copies/ml, and several studies have shown that the likelihood of transmitting the virus through sexual intercourse is negligible at this level.…”
mentioning
confidence: 99%